1997
DOI: 10.1093/humrep/12.2.236
|View full text |Cite
|
Sign up to set email alerts
|

Prorenin and active renin concentrations in plasma and ascites during severe ovarian hyperstimulation syndrome

Abstract: The pathophysiology of ovarian hyperstimulation syndrome (OHSS) remains unclear. Several lines of evidence indicate that OHSS is associated with a stimulation of the renin-angiotensin system (RAS), but its functional significance as well as its role in the pathogenesis of the syndrome are not yet determined. OHSS is associated with high plasma and ascitic concentrations of total renin, renin activity (RA) and angiotensin II (Ang II). Their ovarian or renal origin is, however, still a matter of debate. To clari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…But currently available secondary preventive measures, described below, are far from being ideal. These are [1] delaying hCG injection (coasting), [2] canceling the cycle and withholding hCG injection with or without continuation of GnRHa/GnRH antagonist, [3] aspirating some of the follicles before hCG injection or shortly after hCG injection, [4] decreasing the dose of hCG, [5] use of GnRHa instead of hCG to trigger ovulation in antagonist cycles, [6] use of recombinant LH to trigger ovulation, [7] IV macromolecule administration at the time of oocyte collection, [8] cryopreserving all embryos and postponing ET to a subsequent cycle, and [9] avoiding hCG for luteal phase support. None of the above measures other than cycle cancellation eliminate the risk of OHSS.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…But currently available secondary preventive measures, described below, are far from being ideal. These are [1] delaying hCG injection (coasting), [2] canceling the cycle and withholding hCG injection with or without continuation of GnRHa/GnRH antagonist, [3] aspirating some of the follicles before hCG injection or shortly after hCG injection, [4] decreasing the dose of hCG, [5] use of GnRHa instead of hCG to trigger ovulation in antagonist cycles, [6] use of recombinant LH to trigger ovulation, [7] IV macromolecule administration at the time of oocyte collection, [8] cryopreserving all embryos and postponing ET to a subsequent cycle, and [9] avoiding hCG for luteal phase support. None of the above measures other than cycle cancellation eliminate the risk of OHSS.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma renin level, renin activity, and aldosterone levels have been shown to be increased in OHSS (4,5,11). Chang et al reported a patient with OHSS with internal jugular vein thrombosis who had plasma renin activity nearly 30 times above normal range who returned to normal upon resolution of the syndrome (28).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations